Restoration of Bowel Continuity After Emergency Hartmann’s Procedure - José V. Roig; Marta Aguado; Félix Lluís; Rafael García-Calvo; Javier Aguiló; Juan Hernandis; Míriam Cantos; Francisco Landete; Juan García-Armengol (Journal of Colon And Rectal Cancer, 2016)
Aim: To analyze the factors involved in and the results of stoma reversal after an emergency Hartmann's operation. Methods: A multicenter retrospective study from the Valencian Society of Surgery of patients who had undergone an emergent Hartmann’s operation from 2004 to 2008. An analysis of the reversal rate and related factors, delay, and morbidity of reconstruction was performed. Results: Three hundred sixty-two patients were studied. The most frequent initial diagnosis was colorectal cancer, followed by complicated acute diverticulitis; the primary surgical indication was acute peritonitis. After a median follow-up of 52 months, 151 patients (41.7%) underwent surgery to reverse the stoma at a median of 10 months after initial surgery. Diagnosis of diverticulitis or trauma, peritonitis as the surgical indication, and non-advanced tumors were associated with reversal. Multivariate analysis showed that only age and tumor stage were predictive of reversal. Postoperative complications occurred in 44% of the cases, and wound infection was the most common. There were 9 (6%) anastomotic leaks. Thirteen patients (8.6%) retained a permanent or temporary stoma after the attempted reconstruction. Conclusion: Hartmann’s reversal after emergency surgery is performed in less than half of all such patients and has significant morbidity.
Keywords: Hartmann’s operation